Carbon sequestration in agricultural soils: Issues and strategies - Rao, A. Subba; Jha, Pramod; Biswas, A.K. (Indian Journal of Agroforestry, 2020)
Mechanisms for C stabilization in soils have received much interest recently due to their relevance in the global C cycle. The global soil organic carbon storage corresponds to 615 Gt C in the top 0.2 m depth and 2344 Gt C at depths of up to 3 m, which is more than the combined C content of biomass and atmospheric CO2, It is the largest terrestrial C pool, encompassing approximately two-thirds of the C in ecosystems. Also, mean residence time of soil organic carbon pools have the slowest turnover rates in terrestrial ecosystems and thus C sequestration in soils has the potential to mitigate CO2 emission to the atmosphere. However, soil has definite capacity to capture or sequester organic carbon, beyond which added carbon would escape to the atmosphere. The soil C saturation concept suggests a limit to whole soil organic carbon (SaC) accumulation determined by inherent physicochemical characteristics of soil C pools. The present organic carbon pool in agricultural soils is much lower than their potential capacity. Low sac concentration in Indian soil is attributed to plowing, removal of crop residue and other bio-solids, and mining of soil fertility. The computed carbon sequestration potential of Indian soils by assuming degraded soils to restorative land use is 39 to 49 Tg C y-1. Indian soils have considerable potential of terrestrial/soil carbon sequestration. The estimated soil organic carbon (SaC) pool is 21 Pg in 30 cm depth and 63 Pg in 150 cm depth. The restoration of wastelands, degraded/desertified soils and ecosystems (e.g., afforestation, improved pastures) and adoption of improved farm management practices can enhance soil organic carbon and improve soil quality and soil health. Such management practices include organic agriculture, conservation tillage, mulching, cover crops, integrated nutrient management including use of manure and compost, and agroforestry, as well as improved management of pastures and rangelands. However, the evolving theory of soil carbon saturation suggests that the difference of stabilization deficit should be the priority tool for selection or prioritization of land for soil carbon sequestration strategy. The proportion of carbon stabilized would be greater in samples with larger carbon stabilization deficits and the relative stabilization efficiency would decrease as soil carbon level increase.